KRITERIA PEMILIHAN JENIS KAYU SEBAGAI BAHAN BAKU ALAT MUSIK SARUNEI BERDASARKAN PERSEPSI MASYARAKAT DI KECAMATAN RAYA KABUPATEN SIMALUNGUN SUMATERA UTARA - Shelly Maria Purba; M.Mardhiansyah '; Rudianda Sulaeman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Sarunei is traditional music instrument on Simalungun regency that usually used at Simalungun traditional’s ceremony. This research was aimed to determine what kind of wood’s criteria that community wants as sarunei material in Raya subdistrict. The method used descriptive with quantitative data, through questionnaires and interviews to community of Raya subdistrict determined through snowball sampling. The results of this research indicate that there are 4 wood’s plant that used as sarunei material, such as Codiaeum variegatum BL., Diospyros dalech. ex L., Senna siamea and Solanum torvum. The wood’s priority that community used in Raya subdistrict is Codiaeum variegatum BL. Wood’s criteria that used to sarunei production is a plant that have height ≥2 m, ≥1,8 m diameter, 28-32 cm as wood’s length and straightness level 100%. Keywords: kind of woods, woods criteria, sarunei, community perception.